Investigation of QEEG Waves on Depression and Anxiety: A Systematic Review - Fatih Bal (Pakistan Journal of Medical & Health Sciences, 2022)
This study aims to examine the evaluation of brain waves through Quantitative Electroencephalography in diagnosing and treating depression and anxiety. For this purpose, the keywords "depression, anxiety, QEEG" were scanned in national and international databases. First, all abstracts, titles, and articles in electronic databases were examined, and 181 studies published between 1988-2021 were reached. According to the PRISMA criteria, the articles included in the research were examined by the systematic review method. Five studies were examined due to the evaluation made due to the research. Inclusion criteria in research; It was determined that the studies were between 1988-2021 and included the keywords "depression, anxiety, QEEG". Exclusion criteria were determined as unofficial websites, newspapers, and conference proceedings. According to the results obtained in the study, it was concluded that Quantitative Electroencephalography is an important method used in the diagnosis and treatment of depression and anxiety, which represents the distribution of waves of different frequencies on the brain by analyzing the electrical activity record taken from the scalp, and thus provides indirect information about the functioning of the brain. It is suggested that the research results must be supported by experimental studies with experimental and control groups.